Transportable optical cavity systems for terrestrial and space-borne portable optical atomic clocks - Pal, Rishabh; Yadav, Vikrant; Sharma, Arijit (Frontiers in Quantum Science and Technology, 2024)
High finesse optical cavities have been the backbone of realizing narrow linewidth lasers to drive coherent excitations on dipole-forbidden transitions in atoms and ions for applications in atomic frequency standards. Over the past decade, increasing efforts have been made to develop technologies that enable the operation of all-optical atomic clocks in a portable form factor outside laboratory environments relying on transportable high-finesse optical cavities for field applications in positioning, navigation, timing (PNT) and communication. However, the compactness of such systems makes them more susceptible to environmental noises that limit their performance and stability. This review aims to address the underlying physics behind high-finesse optical cavities, cavity-based laser frequency stabilization schemes and various sources of noise arising from thermal, vibrational, acoustic, power and polarisation fluctuations that impede the stability of portable optical cavities, as well as outline the strategies for minimising their influences. We also discuss about the minimization of the residual amplitude modulation (RAM) noise that degrades the laser linewidth. In addition, our study encompasses a comparative analysis of various transportable, high-finesse optical cavity systems that are currently accessible for terrestrial and space-based metrology applications, as well as an exploration of the potential applications that these cavities can facilitate. We also review recent advancements in designing such systems and highlight their efforts for constructing ultra-stable, compact, high-finesse cavities for terrestrial and space-borne transportable all-optical atomic clocks.